SAMARKAND IS THE CRADLE OF EASTERN SPIRITUALITY AND ITS PLACE IN THE DEVELOPMENT OF WORLD SCIENCE - Mohira Kurbanovna Mirzaeva (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This article analyzes socio-philosophically on the basis of scientific sources that Samarkand as a cradle of Eastern culture and spirituality has become an invaluable heritage of the development of world science and a great foundation for the development of modern science. In addition, scientific conclusions and recommendations for the development of international social, economic and cultural ties as a modern city embodying the traditions of the East will be presented.